Learning the Qur'an After Conversion: Religious Motivation and Qur'anic Engagement among Muslim Converts in Rural Indonesia - Muhammad Zuhri Abu Nawas; Nurthayyibah Nurthayyibah; Teguh Arafah Julianto (Postgraduate Program of the State Islamic Institute of Palopo, 2023)
Religious conversion in Islam extends beyond the formal declaration of faith and involves a continuous process of religious learning and spiritual adaptation. Among the various dimensions of post-conversion religious development, engagement with the Qur’an occupies a central role in strengthening faith and deepening religious understanding. This study aims to examine the religious motivations that encourage Muslim converts to learn the Qur’an and to explore their experiences of Qur’anic engagement in a rural Indonesian context. Employing a qualitative field research design, the study was conducted in Padang Raya Village, Seko District, North Luwu Regency, South Sulawesi. Data were collected through observation, semi-structured interviews, and documentation involving Muslim converts residing in the village. The findings reveal that learning the Qur’an constitutes a significant aspect of the post-conversion journey of Muslim converts. Religious motivation was shaped by both external and internal factors, particularly family support, marital relationships, and personal spiritual aspirations. The study further demonstrates that engagement with the Qur’an extends beyond learning recitation skills and encompasses efforts to understand, internalize, and practice Islamic teachings in everyday life. Participants reported various spiritual benefits derived from Qur’anic learning, including emotional comfort, inner peace, strengthened faith, and increased religious commitment. Despite limited access to formal religious education in this geographically remote area, converts exhibited strong enthusiasm for participating in Qur’anic learning activities. This study contributes to the literature on conversion and Qur’anic engagement by highlighting the role of the Qur’an as a source of religious motivation, spiritual development, and faith sustainability among Muslim converts in rural Indonesia.